Preparation of Soy-Based Adhesive Enhanced by Waterborne Polyurethane: Optimization by Response Surface Methodology - Yong Wang; Layun Deng; Youhua Fan (Advances in Materials Science and Engineering)
Response surface methodology was used to optimize the preparation conditions of soy-based adhesives (SBAs) in this work. The parameters such as the effects and interactions of waterborne polyurethane (WPU) addition level (X1), temperature (X2), and time (X3) on wet shear strength (Y) were investigated. The regression model for SBA preparation was significant (p=0.0034<0.05). The coefficient of determination (R2) of this model was to be 0.9256. According to the results, WPU addition level (X1) had a significant influence on the wet shear strength, whereas reaction temperature (X2) and reaction time (X3) were not significant. The optimal preparation conditions of SBA were 12 wt.% WPU addition level for 101 min at 76°C. Under the optimal conditions, the wet shear strength was 1.07 ± 0.08 MPa, which was in good agreement with the model predicted value. An analysis of FTIR spectra of WPU, soy flour, and soy-based adhesive further confirmed the validity of the model.